Small and medium-sized enterprises failure in providing workers’ rights concerning Sustainable Development Goals-2030 in Pakistan - Naveed, Rana Tahir; Rehmani, Mahmood; Khokhar, Munnawar Naz; Shah, Syed Raza Ullah; Ali, Anis; Shahzadi, Sadaf; Irshad, Huda (Frontiers in Psychology, 2022)
Small and medium-sized enterprises (SMEs) play an enormously crucial part in the modern world economy, demonstrating the most unique and incredible ground-breaking system. SMEs’ employment statistics and future worker needs make it a focus of policies among rising economies, and Pakistan is no exception. The working conditions in SMEs diverge from industry to industry; however, irrespective of the industrial categorization, the SMEs are failing to protect the workers’ rights in the perspective of Sustainable Development Goals (SDGs). The interpretivism paradigm and purposive sampling, narrative inquiry, and analysis method have been adopted to gain in-depth knowledge of workers’ rights in SMEs concerning the SDGs. Results revealed that Pakistan-based SMEs argue to be financially weak and perceived as less equipped to adhere to the world’s standards. Highlighted issues in failure to adhere to worker’s rights include lack of financial resources, top management’s commitment, regulatory framework, SDG awareness, strategic planning, and the dire need for expert guidance and consultation in translating goals to work environments.